Integration of the Values of Surah Al Maun with the STEM Approach as a Learning Model for Muhammadiyah Schools - Nurhadi, Rofiq; Fatmaryanti, Siska Desy; Sert, Hüseyin Emin; Wahyudi, Jarot (Jurnal Tarbiyatuna, 2023)
Developing learning models that are in line with technological advances can build student values and character through the integration of Al-Quran values. One of the surahs in the Al-Quran is surah Al Ma'un, which is strong in instilling social attitudes or concern for the social environment and is the main basis for the Muhammadiyah movement. This research aims to produce a science learning model using a STEM approach containing Al Ma'un and determine the effectiveness of the STEM approach with Al Ma'un as a learning model in improving students' scientific attitudes and social awareness in Muhammadiyah schools. This research is a development research using the Plomp model. The research is conducted at 3 Muhammadiyah Middle Schools in Purworejo Regency. The feasibility of the learning model is carried out by expert validation in terms of syntax, social system, reaction principle, support system, and instructional impact. To test the effectiveness, it uses data on the percentage of pre- and post-observation results. The research results show that the learning model using the STEM approach containing Al Ma'un is valid and suitable for use. The effectiveness of the learning model is also high, based on the percentage increase in students' social awareness and scientific attitudes. This learning model can become an excellent learning model for Muhammadiyah schools. Apart from that, it can also be applied to Islamic schools in general for character development in aspects of social attitudes and social environment.